2016
DOI: 10.1016/j.ttbdis.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transmission of bovine tick-borne pathogens: Frequency, co-infections and fatal neonatal anaplasmosis in a region of enzootic stability in the northeast of Brazil

Abstract: Bovine tick-borne disease (TBD) constitutes a worldwide group of diseases that result in great losses for dairy and beef cattle. With regard to the epidemiological profile of the diseases, the importance of transplacental transmission is still not very well understood. The aim of this study was to determine the transplacental transmission of TBD agents (Anaplasma marginale, Babesia bovis and B. bigemina) in a herd of dairy cattle that had been naturally infected in an area of enzootic stability in northeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…In case reports of clinical neonatal anaplasmosis in cattle as well as in descriptions of experimentally induced neonatal anaplasmosis in cattle, hemoglobinuria or hemoglobinuric nephrosis were not mentioned. 2,7 Another notable difference between our case and cases of neonatal anaplasmosis in other species was the high percentage of infected erythrocytes. In cases of natural and experimentally induced neonatal anaplasmosis in cattle, including experiments with A. centrale, parasitized erythrocytes ranged from <1% to 43%.…”
contrasting
confidence: 53%
“…In case reports of clinical neonatal anaplasmosis in cattle as well as in descriptions of experimentally induced neonatal anaplasmosis in cattle, hemoglobinuria or hemoglobinuric nephrosis were not mentioned. 2,7 Another notable difference between our case and cases of neonatal anaplasmosis in other species was the high percentage of infected erythrocytes. In cases of natural and experimentally induced neonatal anaplasmosis in cattle, including experiments with A. centrale, parasitized erythrocytes ranged from <1% to 43%.…”
contrasting
confidence: 53%
“…Transmission of anaplasmosis was mentioned to be mainly operated by blood sucking dipterous, iatrogenic or vertical transmission in Latin America [ 7 , 34 ]. Vertical transmission would depend on the type of strain involved but infecting until 25% of calves and sometimes causing their death [ 35 , 36 ]. On the other hand, Scoles and collaborators (2008) reported that Dermacentor andersoni was more efficient in transmitting A. marginale than horseflies.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have proved that infected erythrocytes move from infected cows to their offspring through placenta (Zaugg, 1985; Potgieter and Van Rensburg, 1987; Salabarria and Pino, 1988; Costa et al . 2015; Silvestre et al . 2016).…”
Section: Anaplasma Marginalementioning
confidence: 99%